Penerapan Model Direct Instruction untuk Meningkatkan Keterampilan Games Edukasi Siswa Kelas XII - Yanti Hermawati Puji Rahayu (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
The low skill of making educational games on Microsoft Power Point is the basis for this research. Last year's student skill was in the less category. The purpose of this research is to increase skills in making educational games using the Direct Instruction model. The research was conducted through 2 cycles, each consisted of two meetings. Student skill data was taken by the skill observation sheet instrument on indicators: (1) reading the steps for making educational games, (2) determining concepts, (3) making educational games, (4) completing assignments. The success indicator of research that least 24 students (75%) have good skills. The results showed skills from the 16 students (50%) in the sufficient category and 16 students (50%) in the less category in cycle 1, increasing to 28 students (88%) in the good category in cycle 2. Students were able to make educational games using tabs. inserts and hyperlinks. This result can be used by other teachers to fulfill learning requirements.